2009
DOI: 10.1002/gcc.20703
|View full text |Cite
|
Sign up to set email alerts
|

Protocadherin PCDH10, involved in tumor progression, is a frequent and early target of promoter hypermethylation in cervical cancer

Abstract: Cervical cancer (CC) is the second most common cancer in women. Currently no tractable molecular based therapeutic targets exist for patients with invasive CC and no predictive markers of risk assessment for progression of precancerous lesions are identified. New molecular insights into CC pathogenesis are urgently needed. Towards this goal, we first determined the copy number alterations of chromosome 4 and then examined the role of PCDH10 mapped to 4q28 as a candidate tumor suppressor gene. We identified mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 25 publications
2
53
1
Order By: Relevance
“…Although the downregulation of PCDH10 has been reported in a wide range of cancers (6,(9)(10)(11)(12)(13)(14)(15)(16), as far as we know, this is the first study to demonstrate its association with EEC. Our results clearly showed that PCDH10 promoter is hypermethylated through both genomic bisulfite sequencing analysis of locally collected EC samples and analyzing TCGA data from worldwide EEC samples.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Although the downregulation of PCDH10 has been reported in a wide range of cancers (6,(9)(10)(11)(12)(13)(14)(15)(16), as far as we know, this is the first study to demonstrate its association with EEC. Our results clearly showed that PCDH10 promoter is hypermethylated through both genomic bisulfite sequencing analysis of locally collected EC samples and analyzing TCGA data from worldwide EEC samples.…”
Section: Discussionmentioning
confidence: 73%
“…Inactivation of PCDH10 because of promoter CpG hypermethylation has been detected in gastric, hepatocellular, colorectal, breast, cervical, lung, nasopharyngeal, esophageal, pancreatic, and bladder cancer (6,(9)(10)(11)(12)(13)(14)(15)(16). Functional studies revealed that re-expression of PCDH10 inhibits cell growth, reduces clonogenicity, restrains cell invasion, and induces cell apoptosis, substantiating its tumor suppressor roles (10,13,14,16). Moreover, methylation of PCDH10 manifests its significance through its association with clinical parameters.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…55,56 One of the limitations of this study is the moderate clinical sample size with limited samples in the premalignant group. In India, unlike in Western countries, routine screening is not popular, and therefore, few women are diagnosed at the stage of premalignant stage.…”
Section: Discussionmentioning
confidence: 98%
“…PCDH10 downregulation is involved into several types of cancer, including gastric, hepatocellular, colorectal, breast, cervical, lung, nasopharyngeal, esophageal, pancreatic and bladder cancer (30)(31)(32)(33)(34)(35). Functional studies have also identified PCDH10 as a potential novel tumor suppressor gene in multiple types of cancer (18,32,33).…”
Section: Role Of Pcdh10 As a Functional Tsg In Crcmentioning
confidence: 99%